Perishable Food-Inventory Management Improvement Using Single-Period Inventory Model - Muhammad, Kharisma; Anisya Farmaciawaty, Desy (Journal of Innovation, Business and Entrepreneurship, 2018)
Abstract. Rasakhano is a restaurant with perishable inventory. This research was aimed to analyse the inventory in a restaurant, specifically the perishable inventory of Rasakhano restaurant. The main objective of this research is to reach the best optimum supply quantity of perishable ingredients where most of the customers can meet their demand while the restaurant itself still have the very least food waste.  For this research, researcher uses historical sales and inventory data of Rasakhano from July 2017 until November 2017. The data will be processed with single-period inventory model. From the analysis, researcher discovered that the restaurant has the potential of obtaining 59% more possible profit then before. The restaurant also discovered the cost of shortage from each menu to know the cost Rasakhano will put out if there is a certain amount of order that cannot be fulfil. By calculating the cost of overage, the restaurant knows the cost that will be put out if there is a certain amount of menu portion that is not sold in a certain period. The restaurant discovered the optimum stock for each menu to fullfil customers demand while still minimizing the waste of perishable food inventory. Keywords: Inventory Control, Inventory Management, Restaurant, Perishable Inventory, Perishable Food WasteAbstract. Rasakhano is a restaurant with perishable inventory. This research was aimed to analyse the inventory in a restaurant, specifically the perishable inventory of Rasakhano restaurant. The main objective of this research is to reach the best optimum supply quantity of perishable ingredients where most of the customers can meet their demand while the restaurant itself still have the very least food waste.  For this research, researcher uses historical sales and inventory data of Rasakhano from July 2017 until November 2017. The data will be processed with single-period inventory model. From the analysis, researcher discovered that the restaurant has the potential of obtaining 59% more possible profit then before. The restaurant also discovered the cost of shortage from each menu to know the cost Rasakhano will put out if there is a certain amount of order that cannot be fulfil. By calculating the cost of overage, the restaurant knows the cost that will be put out if there is a certain amount of menu portion that is not sold in a certain period. The restaurant discovered the optimum stock for each menu to fullfil customers demand while still minimizing the waste of perishable food inventory. Keywords: Inventory Control, Inventory Management, Restaurant, Perishable Inventory, Perishable Food Waste